2019–2020 Florida Citrus Production Guide: Greasy Spot - Megan M. Dewdney (EDIS)
This 3-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Megan M. Dewdney and published by the Plant Pathology Department, March 2019.